If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2 + -1x) = 3(x + 8) (2 * 7 + -1x * 7) = 3(x + 8) (14 + -7x) = 3(x + 8) Reorder the terms: 14 + -7x = 3(8 + x) 14 + -7x = (8 * 3 + x * 3) 14 + -7x = (24 + 3x) Solving 14 + -7x = 24 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 14 + -7x + -3x = 24 + 3x + -3x Combine like terms: -7x + -3x = -10x 14 + -10x = 24 + 3x + -3x Combine like terms: 3x + -3x = 0 14 + -10x = 24 + 0 14 + -10x = 24 Add '-14' to each side of the equation. 14 + -14 + -10x = 24 + -14 Combine like terms: 14 + -14 = 0 0 + -10x = 24 + -14 -10x = 24 + -14 Combine like terms: 24 + -14 = 10 -10x = 10 Divide each side by '-10'. x = -1 Simplifying x = -1
| (x-4)(5x-3)=0 | | 5.107+0..10(-0.0147058823529)= | | 7(X+9)=9X+5-2X+58 | | -2(3x+3)=2 | | 3*x+2y=16 | | M^2+m=30 | | 4X-5=4(X+5) | | 3y+5y+1y+4y+7+14= | | x+72=3(x-72) | | 2{2a+1/2}=3{a-2/3} | | 4=-5+2y | | -3(2x-3)=3(x+1) | | .3333333333(x-9)=.6666666667 | | 3m^2=48 | | (5X-1)(7X+1)= | | 9-{2k-3}=k | | 1064=(30+x)(20+x) | | 5.107+0.010y=0.35y+5.112 | | 27.95+.12n=.32n+12.95 | | 5x-42=73 | | 9-8p-4=45 | | x-9y=-10 | | 7x+6=4x | | 15c-28=152 | | 3y+4x=14 | | -6g+7g-7=-9 | | 4a-10+3a-5= | | 2z+3+7z=12 | | -5z=8 | | 3(3x-7)=-75 | | 14x-5=11x+4 | | -28+15-22c=31 |